The potential use of chitosan deduced from the results of in silico analysis. Issue 1 (February 2021) - Tallei, T E; Maulana, R R; Windah, A L L; Wahongan, I F; Tumilaar, S G; Fatimawali; Kumaunang, M; Sambul, A M; Adam, A A; Idroes, R
Abstract: One type of coronavirus, SARS-CoV-2, is currently the most feared virus globally because it causes pulmonary infectious diseases that can cause a risk of death. Researchers have tried together by conducting massive research and finding an antidote, especially those sourced from natural ingredients. Chitosan is a natural ingredient isolated from crustaceans. This compound has long been studied and proven to have the ability to inactivate various types of viruses. Therefore, in this study, chitosan's ability to inhibit several proteins and enzymes from SARS-CoV-2 was evaluated in silico . The evaluation results suggested that chitosan has in silico excellent activity in preventing the entry of SARS-CoV-2 into the cells and inhitibing its replication.